Stuck in the Maze: Syrian Unaccompanied Children Navigating Spheres of Protection in Egypt - Pelletier de chambure, Anouk (AUC Knowledge Fountain, 2025)
This research explores the protection of Syrian unaccompanied and separated children (UASC) in Egypt who have fled the Syrian conflict and reflects on the role of formal protection providers and informal networks of solidarity. In hopes of pushing back against the over- essentialization of UASC as vulnerable children, this research unravels the lived experiences of seven aged-out Syrian UASCs who have been living in Egypt for a few years, which reveals their authentic and original crafting of spheres of protection. This thesis aims to contribute to a more extensive and more accurate understanding of the lives and needs of Syrian youth and UASC, arguing that a more significant effort to rethink refugee protection, in general, is needed. Through a qualitative approach, the research unpacks the circumstances that led each participant to leave Syria and choose Egypt as a new country to settle in, their daily lives marked by forced independence, the support they’ve received from different protection stakeholders, and their hopes for the future: stay, move, or return.